Characterizing Tropical Cyclones in the Energy Exascale Earth System Model Version 1. (8th August 2020) - Balaguru, Karthik; Leung, L. Ruby; Van Roekel, Luke P.; Golaz, Jean‐Christophe; Ullrich, Paul A.; Caldwell, Peter M.; Hagos, Samson M.; Harrop, Bryce E.; Mametjanov, Azamat
Abstract: In this study, we analyze the realism with which tropical cyclones (TCs) are simulated in the fully coupled low‐ and high‐resolution Energy Exascale Earth System Model (E3SM) version 1, with a focus on the latter. Compared to the low‐resolution (grid spacing of ∼1°), the representation of TCs improves considerably in the high‐resolution configuration (grid spacing of ∼0.25°). Significant improvements are found in the global TC frequency, TC lifetime maximum intensities, and the relative distribution of TCs among the different basins. However, at both resolutions, spurious TC activity is found in some basins, notably in the subtropical regions. Contrasting the simulated large‐scale TC environment with observations reveals that the model environment is unrealistically conducive for TC development in those regions. Further analysis indicates that these biases are likely related to those in thermodynamic potential intensity, caused by systematic SST biases, and vertical wind shear in the coupled model. TC‐ocean interaction is also examined in the high‐resolution configuration of the model. The salient features of the ocean's response to TC‐induced mixing and the ocean's impact on TC intensification are well‐reproduced. Finally, an evaluation of the influence of El Niño Southern Oscillation (ENSO) on TCs in the high‐resolution configuration of the model reveals that the ENSO‐TC relationship in the model has the right sign and is significant for the North Atlantic and Northwest Pacific, albeit weaker than in observations. In summary, the high‐resolution configuration of the E3SM model simulates TC activity reasonably and hence could be a useful tool for TC‐related research. Plain Language Summary: Considering the wide range of spatiotemporal scales governing tropical cyclones (TCs), high‐resolution numerical models that can resolve both small‐scale and large‐scale processes are needed to simulate TCs realistically. In this study, we describe the simulation of TCs in version 1 of the U.S. Department of Energy's Energy Exascale Earth System Model (E3SM) model with a focus on results from the high‐resolution configuration (spatial resolution of 0.25° in the atmosphere). When compared to the simulation at the low or standard resolution configuration (spatial resolution of 1° in the atmosphere), the salient features of TCs, such as their frequency distribution among the various basins and their strength, improve considerably in the high‐resolution configuration, underlining the value of high‐resolution modeling. Further, the high‐resolution configuration of the model realistically simulates the interaction between TCs and the ocean beneath them, which is a fundamental aspect of their development. However, our analysis also reveals that systematic errors in the simulated climate can cause misrepresentation of the model TC environment, leading to spurious TC activity in certain regions and a weaker control exerted by El Niño‐Southern Oscillation. Overall, the high‐resolution E3SM well represents the global TC climatology, supporting it as a valuable tool for studying TCs. Key Points: Under a variety of metrics, simulated TCs are significantly improved in high‐resolution versus low‐resolution E3SM configurations Spurious TC activity in the model can be well‐explained by errors in the simulation of sea surface temperatures and the vertical wind shear TC‐induced oceanic cooling and the ocean's negative feedback on TCs are well‐simulated in the high‐resolution configuration of the model